2007
DOI: 10.2134/jeq2006.0025
|View full text |Cite
|
Sign up to set email alerts
|

Five Year‐Round Forage Systems in a Dairy Effluent Sprayfield

Abstract: In northern Florida, forages are grown in dairy effluent sprayfields to recover excess P. Our purpose was to evaluate five year-round forage systems for their capacity to remove P from a dairy sprayfield. The soil is a Kershaw sand (thermic, uncoated Typic Quartzipsamment). Systems included bermudagrass (Cynodon spp.)-rye (Secale cereale L.) (BR), perennial peanut (Arachis glabrata Benth.)-rye (PR), corn (Zea mays L.)-forage sorghum [Sorghum bicolor (L.) Moench]-rye (CSR), corn-bermudagrass-rye (CBR), and corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…During the establishment year (2007), elephantgrass yields were 95 and 32% greater than stargrass and switchgrass, respectively. Elephantgrass, stargrass, and switchgrass DM yields were consistent with previous reports under similar environmental conditions (Woodard and Prine, 1993; Mislevy, 2006; Newman et al, 2009a, 2009b; Woodard et al, 2007). Despite its high yield potential in other regions in the United States (Hall et al, 1982; Muir et al, 2001), switchgrass demonstrated poor adaptability to the soil and environmental conditions and only persisted during the first 2 yr of the study (2007 and 2008).…”
Section: Resultssupporting
confidence: 91%
“…During the establishment year (2007), elephantgrass yields were 95 and 32% greater than stargrass and switchgrass, respectively. Elephantgrass, stargrass, and switchgrass DM yields were consistent with previous reports under similar environmental conditions (Woodard and Prine, 1993; Mislevy, 2006; Newman et al, 2009a, 2009b; Woodard et al, 2007). Despite its high yield potential in other regions in the United States (Hall et al, 1982; Muir et al, 2001), switchgrass demonstrated poor adaptability to the soil and environmental conditions and only persisted during the first 2 yr of the study (2007 and 2008).…”
Section: Resultssupporting
confidence: 91%
“…A detailed description of the pivot design and site layout has been reported by Woodard et al (2007) In their study, forages of five year‐round systems were grown in a dairy effluent sprayfield and irrigated with three effluent loading rates (low, medium, and high) over five consecutive 12‐mo cycles (1996–2001). The current study involves soil and soil water data collected over the last three 12‐mo cycles (1998–2001).…”
Section: Methodsmentioning
confidence: 99%
“…Results were inconclusive and will not be addressed. We think that the relatively small differences in soil P removed among systems (Woodard et al, 2007) were obscured by the large, variable amount of P present in the topsoil at the start of the project. Therefore, the effects of effluent rate, soil depth, and period (time) were analyzed across forage systems.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, Tifton-85 offers hay production and heavy grazing potential in the year of establishment, whereas most other cultivars do not produce high yields until the 2nd year. In research trials, Tifton 85 has produced among the highest dry matter (DM) yields with greater quality when compared to other grasses under diverse management and environmental conditions [3,5,6,7,8], making it an ideal forage for dairy and beef in the southern US [2,7]. Since its release in 1993, Tifton 85 has been increasing in popularity among hay and cattle producers in the southern US, Central and South America, and Southern Africa.…”
Section: Introductionmentioning
confidence: 99%